2014
DOI: 10.1186/1471-244x-14-75
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of psychosis in epilepsy; a systematic review and meta-analysis

Abstract: BackgroundEpilepsy has long been considered to be a risk factor for psychosis. However there is a lack of consistency in findings across studies on the effect size of this risk which reflects methodological differences in studies and changing diagnostic classifications within neurology and psychiatry. The aim of this study was to assess the prevalence of psychosis in epilepsy and to estimate the risk of psychosis among individuals with epilepsy compared with controls.MethodsA systematic review and meta-analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
152
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(174 citation statements)
references
References 70 publications
12
152
1
9
Order By: Relevance
“…Some studies revealed the correlation between psychosis and epilepsy and found that the prevalence rate for psychosis in epilepsy patients was about 5.6%. 8 Present study was conducted among the patients attended at a tertiary care hospital of Bangladesh and relatively smaller sample. So, studies covering the larger sample sizes, including multiple centers, evaluation of the community peoples, and assessment in primary care setting would be better to generalize the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies revealed the correlation between psychosis and epilepsy and found that the prevalence rate for psychosis in epilepsy patients was about 5.6%. 8 Present study was conducted among the patients attended at a tertiary care hospital of Bangladesh and relatively smaller sample. So, studies covering the larger sample sizes, including multiple centers, evaluation of the community peoples, and assessment in primary care setting would be better to generalize the results.…”
Section: Discussionmentioning
confidence: 99%
“…7 Epilepsy has long been considered to be a risk factor for psychosis. 8 There are also increased risks for developing other psychiatric co-morbidities. Though the increased prevalence of behavioral problems has often been documented in children with chronic seizures, several studies have also shown an increased prevalence of behavioral problems in children with new-onset or recent-onset seizures.…”
mentioning
confidence: 99%
“…27,28 A systematic review and meta-analysis found a 7.8-fold increased risk of psychosis in individuals with epilepsy. 29 Additional to shared genetics, patients with epilepsy and ASD have frequent contacts with health care. Thus, we cannot rule out that surveillance bias (also present in relatives) has contributed to the excess risks witnessed in our study.…”
mentioning
confidence: 99%
“…According to a recent meta-analysis, pooled prevalence of psychosis in epilepsy is 5.6%, and 7% in temporal lobe epilepsy [8]. This rate is found to be 7.8 times higher than in people without epilepsy [8].…”
Section: Discussionmentioning
confidence: 99%